Bio-optical investigation of phytoplankton production in the southern Benguela ecosystem - Lamont, Tarron (Department of Oceanography, 2015)
This study aims to evaluate various existing models for the estimation of PP in the southern Benguela ecosystem, and to investigate the photophysiological responses of phytoplankton to changes in environmental conditions.